Rationale for the surgical treatment of pulmonary metastases. Issue 9 (September 1981) - Marks, P; Ferrag, M Z; Ashraf, H
Abstract : In a twenty-six year period, 90 patients underwent surgical treatment for metastatic malignant disease of the lung. The primary tumour had apparently been completely removed and there was no evidence of other metastatic spread. Thirty patients enjoyed a survival of more than five years. In 22 cases of the lung lesion was multiple and in 17, the lesions were bilateral. In patients with pulmonary metastases, but without evidence of other dissemination of the disease, resection of the lesions provided useful palliation, and 33% survived for five years of more.